The contributions to the human dorsal column tracts from the spinal cord laminae - (:unkn) unknown (IMPERIAL COLLEGE PRESS, 2016)
The dorsal column tracts (fasciculus gracilis and fasciculus cuneatus) are concerned with discriminative qualities of sensation. There are controversial descriptions related to the relations of dorsal column tracts with the dorsal horn laminae in text-books. The present study aims to define the laminae of the dorsal horn of the spinal cord that contribute fibers to the dorsal column tracts in the cervical, thoracic and lumbar spinal level. Series paraffin spinal cords sections of six formalin-embalmed adult human cadavers were evaluated. The present study shows that dorsal column tracts receive fiber contributions from laminae III and V and from Clarke's dorsal nucleus at varying spinal levels. At upper cervical levels (C1-C4) fiber contributions were from lamina V and few from lamina III, and at lower cervical levels (C5-C8) there were, in addition to these laminae, also contributions from the Clarke's dorsal nucleus. At upper thoracic levels (T1-T4) fiber contributions were from lamina V and few from Clarke's dorsal nucleus. At lower thoracic (T5-T12) and lumbar levels (L1-L5), in contrast, fiber contributions were only from Clarke's dorsal nucleus. The detailed knowledge of organization of the dorsal column tracts of the spinal cord may pave the way for future treatments of the spinal cord injuries.
Keywords: Dorsal funiculus; dorsal column; ascending pathways; fasciculus cuneatus and gracilis; RAT; REGENERATION; TERMINATION; NEURONS; INJURY; FIBERS; GAP-43